Crosslinked product of fluorine-containing copolymer and fluorine-containing copolymer composition
By introducing fluorine-containing copolymers with indole ring structure into FFKM crosslinked rubber, the problem of insufficient heat resistance at high temperatures in the prior art is solved, and the effect of excellent short-term and long-term heat resistance of the rubber is achieved.
Patent Information
- Application Number
- CN202380050451.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-06
- Filing Date
- 2023-06-21
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to maintain the short-term and long-term heat resistance of FFKM crosslinked rubber at higher temperatures.
By introducing fluorine-containing copolymers with indole ring structures, a crosslinking structure containing indole rings is formed using specific structural units and crosslinking agents, thereby improving the heat resistance of the rubber.
It has achieved excellent short-term and long-term heat resistance of FFKM crosslinked rubber, and can maintain good mechanical properties at high temperatures of around 300°C.
Smart Images

Figure BDA0005214001550000031 
Figure BDA0005214001550000051 
Figure BDA0005214001550000071
Abstract
Description
Technical Field
[0001] The present invention relates to a crosslinked product of a fluorinated copolymer and a fluorinated copolymer composition for obtaining the crosslinked product. Background Art
[0002] FFKM is a fluorinated copolymer containing tetrafluoroethylene (TFE) and perfluoroalkyl vinyl ethers such as perfluoromethyl vinyl ether (PMVE) as monomer structural units, and is also called a perfluoroelastomer. The rubber obtained by cross-linking FFKM has excellent heat resistance and chemical resistance, and is therefore widely used in semiconductor manufacturing, vehicles, aircraft, general machinery, construction, chemical plants, etc. as sealing materials such as O-rings, washers, oil seals, gaskets, and cushioning materials.
[0003] As a crosslinking method, for example, a method is known in which a peroxide such as 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane is used as a crosslinking agent to cause crosslinking at the terminal iodine atom of the monomer. Furthermore, from the viewpoint of increasing the crosslinking reaction rate, it is also proposed to use a bismaleimide compound as a crosslinking aid (see Patent Document 1).
[0004] Also known is a method of introducing a fluorine-containing compound having a nitrile group as a monomer structural unit into FFKM and using tetraphenyltin as a catalyst to form a crosslinked structure including a triazine ring by trimerization of the nitrile group (see, for example, Patent Document 2).
[0005] Furthermore, from the viewpoint of reducing the compression set of the cross-linked product at a high temperature of about 300°C, it has been proposed to introduce a fluorinated compound having a nitrile group into FFKM as a monomer structural unit, and to use a bisaminophenol compound such as 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane as a cross-linking agent to form a cross-linked structure containing an oxazole ring (see Patent Documents 3 and 4).
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: International Publication No. 2021 / 166664
[0009] Patent Document 2: Japanese Patent Publication No. 63-5409
[0010] Patent Document 3: Japanese Patent Publication No. 2-59177
[0011] Patent Document 4: International Publication No. 2021 / 210503 Summary of the invention
[0012] Problem that the invention aims to solve
[0013] As the use of rubber in various industries expands, rubber properties that can be exhibited at higher temperatures are required. It is also desired that the heat resistance of rubber obtained by crosslinking FFKM be further improved.
[0014] However, even the rubbers described in Patent Documents 1 to 4 cannot necessarily be said to have fully satisfactory short-term heat resistance and long-term heat resistance.
[0015] The present invention has been made in view of such circumstances, and an object of the present invention is to provide a cross-linked product of a fluorinated copolymer excellent in both short-term heat resistance and long-term heat resistance, and a fluorinated copolymer composition suitable for obtaining such a cross-linked product.
[0016] Solutions for solving problems
[0017] The present invention is based on the finding that both short-term heat resistance and long-term heat resistance are excellent when a cross-linked fluorinated copolymer has an indole ring.
[0018] The present invention provides the following means.
[0019] [1] A cross-linked product of a fluorinated copolymer having an indole ring.
[0020] [2] The cross-linked product of the fluorinated copolymer according to [1], wherein the fluorinated copolymer comprises a structural unit (C) derived from a fluorinated compound having a carbon-carbon double bond and a -C(=O)CH2- group.
[0021] [3] The cross-linked product of the fluorinated copolymer according to [2], wherein the content of the structural unit (C) is 0.1 to 20 mass % in 100 mass % of the total monomer structural units of the fluorinated copolymer.
[0022] [4] A cross-linked product of a fluorinated copolymer according to [2] or [3], wherein the fluorinated copolymer comprises at least one of a structural unit (A) and a structural unit (B), wherein the structural unit (A) is derived from tetrafluoroethylene and the structural unit (B) is derived from at least one of a perfluoroalkyl vinyl ether and a perfluorobutenyl vinyl ether.
[0023] [5] The cross-linked product of the fluorinated copolymer according to [4], wherein, in the total of 100 mass% of the structural units (A) to (C) of the fluorinated copolymer, the structural unit (A) accounts for 29.9 to 80 mass%, the structural unit (B) accounts for 19.9 to 70 mass%, and the structural unit (C) accounts for 0.1 to 20 mass%.
[0024] [6] The cross-linked product of the fluorinated copolymer according to [4], wherein, in 100% by mass of the total of the structural units (A) to (C), the structural unit (A) accounts for 80 to 99.9% by mass, the structural unit (B) accounts for 0 to 19.9% by mass, and the structural unit (C) accounts for 0.1 to 20% by mass.
[0025] [7] The cross-linked product of the fluorinated copolymer according to [4], wherein, in 100% by mass of the total of the structural units (A) to (C), the structural unit (A) accounts for 0 to 49.9% by mass, the structural unit (B) accounts for 50 to 99.9% by mass, and the structural unit (C) accounts for 0.1 to 10% by mass.
[0026] [8] A fluorinated copolymer composition comprising a fluorinated copolymer and a compound (D), wherein the fluorinated copolymer comprises a structural unit (A) derived from tetrafluoroethylene, a structural unit (B) derived from at least any one of a perfluoroalkyl vinyl ether and a perfluorobutenyl vinyl ether, and a structural unit (C) derived from a fluorinated compound having a carbon-carbon double bond and a -C(=O)CH2- group, and the compound (D) has two or more structures (d) represented by the following formula (1).
[0027]
[0028] In formula (1), -a 1 represents a single bond, which is bonded to a hydrogen atom, a methyl group, or an aromatic ring which may have a substituent. 1 ~-b 5 Respectively represent single bonds, -b 1 and -b 5 At least one of them is bonded to a hydrogen atom. In addition, the benzene ring in the formula (1) is referred to as benzene ring A.
[0029] [9] The fluorinated copolymer composition according to [8], wherein the compound (D) has one or more structures in which one benzene ring A of the structure (d) is linked to another benzene ring A of the structure (d) via a single bond.
[0030]
[10] The fluorinated copolymer composition according to [8] or [9], wherein the content of the compound (D) is from 0.1 to 10 parts by mass based on 100 parts by mass of the fluorinated copolymer.
[0031] Effects of the Invention
[0032] According to the present invention, there can be provided a cross-linked product of a fluorinated copolymer excellent in both short-term heat resistance and long-term heat resistance, and a fluorinated copolymer composition suitable for obtaining such a cross-linked product. DETAILED DESCRIPTION
[0033] The definitions and meanings of the terms and expressions in this specification are shown below.
[0034] "Room temperature" refers to 20-25°C.
[0035] “Short-term heat resistance” means that mechanical properties, especially storage modulus, hardly change when heated from room temperature to about 300° C. in a test based on the “tensile vibration-non-resonance method” specified in JIS K 7244-4:1999. Specifically, it is evaluated by the thermomechanical analysis method described in the Examples.
[0036] “Long-term heat resistance” means that mechanical properties are maintained for 72 hours or more at a high temperature of about 300° C. Specifically, the evaluation is performed by the hanging method described in the Examples.
[0037] The content of the monomer structural unit in the fluorinated copolymer is determined by a nuclear magnetic resonance (NMR) measuring apparatus. 1 H-NMR and 19 The value calculated from the measurement result of F-NMR. Specifically, it is determined by the method described in the Examples.
[0038] [Cross-linked fluorinated copolymer]
[0039] The cross-linked product of the fluorinated copolymer according to the embodiment of the present invention (hereinafter also referred to as "the cross-linked product of the present embodiment") has an indole ring. The cross-linked product of the present embodiment preferably has a cross-linked structure including an indole ring.
[0040] The crosslinked product containing a ring structure in the crosslinked structure tends to have excellent heat resistance compared to the crosslinked product without a ring structure. In addition, when the ring structure contained in the crosslinked structure is an indole ring, it can obtain better heat resistance than when the ring structure is a benzene ring, an oxazole ring, or a triazine ring. In particular, both short-term heat resistance and long-term heat resistance are excellent.
[0041] The fluorinated copolymer (hereinafter also referred to as fluorinated copolymer) used to form the crosslinked product of the present embodiment preferably contains a structural unit (C) derived from a fluorinated compound having a carbon-carbon double bond and a -C(=O)CH2- group. The monomer forming the structural unit (C) may be a single monomer or a combination of two or more monomers.
[0042] As the monomer forming the structural unit (C), for example, a monomer shown in the following formula (2) can be cited. The compound is a novel fluorinated compound having a carbonyl group and a vinyl or fluorovinyl group as a polymerizable unsaturated bond in the main chain. By introducing such a fluorinated compound as a monomer structural unit into, for example, FFKM, a cross-linked structure containing an indole ring is easily formed, and a fluorinated polymer suitable for obtaining a cross-linked product having excellent short-term heat resistance and long-term heat resistance can be constituted.
[0043]
[0044] In formula (2), R 1 ~R 3 Each independently represents a hydrogen atom or a fluorine atom. From the viewpoint of polymerization reactivity, preferably all of them are hydrogen atoms or all of them are fluorine atoms. From the viewpoint of heat resistance, more preferably all of them are fluorine atoms.
[0045] R 4 It is a hydrogen atom, a fluorine atom, or a monovalent organic group having 1 to 8 carbon atoms without a carbonyl group. From the viewpoint of the ease of synthesis of the fluorine-containing compound of the present embodiment, the number of carbon atoms of the organic group is preferably 1 to 7, more preferably 1 to 6, and further preferably 1 to 5. The organic group may be any of linear, branched or cyclic, preferably linear or branched. The organic group may contain heteroatoms such as nitrogen atoms, oxygen atoms or sulfur atoms.
[0046] For R 4 , although it depends on the crosslinking agent used, from the viewpoint of becoming a crosslinking site for forming a crosslinked structure containing an indole ring in the fluorinated copolymer, preferably a hydrogen atom, that is, the fluorinated compound preferably has a crosslinking site containing R at the molecular end. 4 of acetyl.
[0047] Z is an oxygen atom, a sulfur atom or -N(R 5 )-, R 5 It is a hydrogen atom or a monovalent organic group having 1 to 4 carbon atoms. From the viewpoint of the ease of synthesis of the fluorine-containing compound, the number of carbon atoms of the organic group is preferably 1 to 3, more preferably 1 or 2, and further preferably 1. The organic group may be any of linear, branched or cyclic, preferably linear or branched. The organic group may contain heteroatoms such as nitrogen atoms, oxygen atoms or sulfur atoms.
[0048] From the viewpoint of good rubber properties of a cross-linked product of the fluorinated copolymer, Z is preferably an oxygen atom or a sulfur atom, more preferably an oxygen atom.
[0049] X is a single bond or a difluoromethylene group, and is preferably a single bond from the viewpoint of ease of synthesis of the fluorine-containing compound of the present embodiment.
[0050] Y 1 ~Y 4 Each independently represents a fluorine atom or a trifluoromethyl group. From the viewpoint of polymerization reactivity and heat resistance, Y 1 and Y 3 They are fluorine atoms, and from the viewpoint of the ease of synthesis of the fluorine-containing compound of the present embodiment, they are more preferably all fluorine atoms.
[0051] Q is a perfluoroalkylene group having 1 to 8 carbon atoms and optionally containing an etheric oxygen atom. From the viewpoint of ease of synthesis of the fluorine-containing compound, the perfluoroalkylene group preferably has 1 to 7 carbon atoms, more preferably 1 to 6 carbon atoms. When containing an etheric oxygen atom, the number of oxygen atoms is preferably 1 to 3, more preferably 1 or 2, and further preferably 1. Q may be linear or branched, and is preferably linear.
[0052] From the viewpoint of ease of synthesis of the fluorine-containing compound, Q is preferably a perfluoroalkylene group, and particularly preferably a group having 1 carbon atom, that is, a difluoromethylene group.
[0053] Specific examples of the compound represented by formula (2) include CF2=CFO(CF2)2(C=O)CH3, CF2=CFO(CF2)3(C=O)CH3 (hereinafter also referred to as CSM-1), CF2=CFO(CF2)4(C=O)CH3, CF2=CFO(CF2)3O(CF2)2(C=O)CH3, CF2=CFOCF2C(CF3)FO(CF2)2(C=O)CH3, CF2=CFOCF2C(CF3)FO(CF2)3(C=O)CH3, etc. Among these, CSM-1 is preferred from the viewpoint of ease of synthesis.
[0054] The fluorine-containing compound as described above can be obtained by, for example, reacting a perfluorovinyloxy polyether carboxylic acid or a derivative thereof with a Grignard reagent, an organic lithium reagent, or the like to generate a ketone. As carboxylic acid derivatives, for example, esters, carboxylic acid halides, etc. can be cited. For example, when a Grignard reagent (organic magnesium halide: general formula RMgX) is used, the following method can be applied: a synthetic method in which a substituent (terminal group) bonded to a carbonyl group of a perfluorovinyloxy polyether carboxylic acid or a derivative thereof is substituted with an organic group R of a Grignard reagent. Specifically, it can be synthesized using the method described in the examples, and can also be obtained as a commercially available product.
[0055] Examples of the monomer forming the structural unit (C) include, in addition to the fluorinated compound represented by the formula (2), perfluorovinyl ether having an iodine atom at the terminal and perfluorovinyl ether acid halide as represented by the following formula, which are also commercially available.
[0056]
[0057] The fluorinated copolymer for forming the cross-linked product of the present embodiment preferably contains, in addition to the structural unit (C), at least one of the structural unit (A) and the structural unit (B), wherein the structural unit (A) is derived from tetrafluoroethylene (TFE) and the structural unit (B) is derived from at least one of perfluoroalkyl vinyl ether (PAVE) and perfluorobutenyl vinyl ether (PBVE).
[0058] By introducing the structural unit (C) derived from the fluorinated compound into the fluorinated copolymer having PAVE or PBVE as a monomer structural unit, a cross-linked product of the fluorinated copolymer excellent in both short-term heat resistance and long-term heat resistance can be obtained.
[0059] The monomer forming the structural unit (A) is TFE.
[0060] The monomer forming the structural unit (B) is at least one of PAVE and PBVE. The monomer forming the structural unit (B) may be used alone or in combination of two or more.
[0061] From the viewpoint of good polymerization reactivity and rubber properties, the number of carbon atoms in the perfluoroalkyl group of PAVE is preferably 1 to 10, more preferably 1 to 8, further preferably 1 to 6, further preferably 1 to 5, and particularly preferably 1 to 3. The perfluoroalkyl group may be linear or branched.
[0062] As the specific example of PAVE, perfluoromethyl vinyl ether (PMVE), perfluoroethyl vinyl ether (PEVE), perfluoro n-propyl vinyl ether (PPVE) etc. can be listed. PAVE can be a single kind, or two or more kinds can be used in combination. Among these, from the viewpoint of polymerization reactivity, PMVE, PEVE are preferably used, and PMVE is more preferably used.
[0063] Regarding the fluorinated copolymer for forming the cross-linked product of the present embodiment, from the viewpoint of good heat resistance and rubber properties of the cross-linked product, the content of the structural unit (C) is preferably 0.1 to 20 mass %, more preferably 0.2 to 15 mass %, further preferably 0.5 to 10 mass %, based on 100 mass % of the total monomer structural units of the fluorinated copolymer.
[0064] In the fluorinated copolymer, in addition to the structural units (A) to (C), there may also be structural units based on other monomers. From the viewpoint of the heat resistance of the crosslinked product of the fluorinated copolymer of the present embodiment, the total amount of the other monomer structural units is preferably 0 to 20% by mass, more preferably 0 to 15% by mass, and further preferably 0 to 10% by mass relative to the total of 100% by mass of all monomer structural units of the fluorinated copolymer. It is most preferred that no other monomers are contained.
[0065] The fluorinated copolymer preferably contains 29.9 to 80 mass % of the structural unit (A), 19.9 to 70 mass % of the structural unit (B), and 0.1 to 20 mass % of the structural unit (C) in 100 mass % of the total of the structural units (A) to (C).
[0066] The content of the structural unit (A) is preferably 29.9 to 80 mass %, more preferably 38.8 to 75 mass %, and even more preferably 45.5 to 70 mass % in 100 mass % of the total of the structural units (A) to (C).
[0067] The content of the structural unit (B) is preferably 19.9 to 70 mass %, more preferably 24.8 to 60 mass %, and even more preferably 29.5 to 50 mass % in 100 mass % of the total of the structural units (A) to (C).
[0068] The content of the structural unit (C) is preferably 0.1 to 20 mass %, more preferably 0.2 to 15 mass %, and even more preferably 0.5 to 10 mass % in 100 mass % of the total of the structural units (A) to (C).
[0069] The fluorinated copolymer may contain 80 to 99.9 mass % of the structural unit (A), 0 to 19.9 mass % of the structural unit (B), and 0.1 to 20 mass % of the structural unit (C) in 100 mass % of the total of the structural units (A) to (C).
[0070] As described above, even in a fluorinated copolymer containing TFE as a main component occupying more than 80 mass % and containing no structural unit (B) or containing a very small amount thereof, the cross-linked product of the present embodiment can obtain good heat resistance.
[0071] The fluorinated copolymer may contain 0 to 49.9 mass % of the structural unit (A), 50 to 99.9 mass % of the structural unit (B), and 0.1 to 10 mass % of the structural unit (C) in 100 mass % of the total of the structural units (A) to (C).
[0072] As described above, even in a fluorinated copolymer in which the monomer forming the structural unit (B) is the main component and TFE structural unit is not contained or the amount thereof is less than that of the structural unit (B), the cross-linked product of the present embodiment can obtain good heat resistance.
[0073] Examples of other monomers forming structural units other than structural units (A) to (C) include vinylidene fluoride, chlorotrifluoroethylene, hexafluoropropylene, a fluorine-containing monomer having two polymerizable unsaturated groups (hereinafter referred to as "DVM"), 2,3,3,3-tetrafluoro-1-propylene, hydrocarbon monomers, etc. The other monomers may be either a single monomer or two or more monomers.
[0074] From the viewpoint of heat resistance of the cross-linked product of the present embodiment, DVM is preferably a compound represented by the following formula (3): By using DVM having two polymerizable unsaturated groups as a monomer, a fluorinated copolymer having a branch can be obtained.
[0075] (CR21 R 22 =CR 23 )2R 24 (3)
[0076] In formula (3), R 21 , R 22 and R 23 Each R is independently a hydrogen atom, a fluorine atom, a methyl group or a trifluoromethyl group. 21 , R 22 and R 23 They may be the same or different, but are preferably the same. From the viewpoint of polymerization reactivity, R 21 , R 22 and R 23 Preferably, they are hydrogen atoms or fluorine atoms, more preferably, they are both hydrogen atoms or both fluorine atoms, and further preferably, they are both fluorine atoms from the viewpoint of heat resistance.
[0077] R 24 is a perfluoroalkylene group having 1 to 10 carbon atoms, which may contain an etheric oxygen atom. The perfluoroalkylene group preferably has 1 to 8 carbon atoms, more preferably 1 to 6 carbon atoms, and even more preferably 1 to 4 carbon atoms. When containing an etheric oxygen atom, the number of oxygen atoms is preferably 1 to 3, more preferably 1 or 2, and even more preferably 1. R 24 It may be linear, branched, or cyclic, preferably linear or branched, and more preferably linear.
[0078] Specific examples of DVE include CF2=CFO(CF2)2OCF=CF2, CF2=CFO(CF2)3OCF=CF2, CF2=CFO(CF2)4OCF=CF2, CF2=CFO(CF2)6OCF=CF2, CF2 =CFO(CF2)8OCF=CF2, CF2=CFO(CF2)2OCF(CF3)CF2OCF=CF2, CF2=CFO(CF2)2O(CF(CF3)CF2O)2CF=CF2, CF2=CFOCF2O(CF2C F2O)2CF=CF2, CF2=CFO(CF2O)3(CF(CF3)CF2O)2CF=CF2, CF2=CFOCF2CF(CF3)O(CF2)2OCF(CF3)CF2OCF=CF2, CF2=CFOCF2C F2O(CF2O)2CF2CF2OCF=CF2, CF2=CFO(CF2)2CF=CF2, CH2=CH(CF2)2CH=CH2, CH2=CH(CF2)4CH=CH2, CH2=CH(CF2)6CH=CH2, etc. Among these, CF2=CFO(CF2)3OCF=CF2, CF2=CFO(CF2)4OCF=CF2 or CH2=CH(CF2)6CH=CH2 is preferred.
[0079] Examples of the hydrocarbon monomer include olefins such as ethylene, propylene, isobutylene, and 1-butene.
[0080] [Method for producing fluorinated copolymer]
[0081] The fluorinated copolymer is obtained by copolymerizing monomers constituting structural units by emulsion polymerization, solution polymerization, suspension polymerization or the like in the presence of a radical polymerization initiator, and the production method is not particularly limited.
[0082] As the radical polymerization initiator, a known radical polymerization initiator can be used in the production of a fluorinated copolymer, and the radical polymerization initiator can be appropriately selected according to the polymerization method.
[0083] In the emulsion polymerization in an aqueous medium such as water, a water-soluble free radical polymerization initiator is preferred, and examples thereof include persulfates such as ammonium persulfate, sodium persulfate, potassium persulfate, disuccinic acid peroxide, azobisisobutyramidine dihydrochloride, tert-butyl hydroperoxide, peroxydicarbonates, etc. Among these, persulfates are preferred, and ammonium persulfate is more preferred. In addition, a redox polymerization initiator realized by a combination of persulfates or hydrogen peroxide with a reducing agent such as sodium bisulfite or sodium thiosulfate may also be used in combination; a small amount of metals or metal compounds such as iron, ferrous salts, and silver sulfate may be further used in combination with the redox polymerization initiator.
[0084] As a radical polymerization initiator in solution polymerization using a solvent such as 1H-perfluorohexane, for example, an organic peroxide such as bis(pentafluoropropionyl)peroxide, pivaloyl tert-butyl peroxide, and diisopropyl peroxydicarbonate can be used.
[0085] The radical polymerization initiator may be added all at once or sequentially. The amount of the radical polymerization initiator used is preferably 0.0001 to 3 parts by mass, more preferably 0.001 to 2 parts by mass, and even more preferably 0.01 to 1 part by mass, based on 100 parts by mass of all monomers to be polymerized.
[0086] In order to adjust the moldability and mechanical properties of the fluorinated polymer, a chain transfer agent can be added to the reaction system. Examples of chain transfer agents include saturated hydrocarbon compounds such as hexane and cyclohexane; aromatic compounds containing alkyl groups such as xylene and ethylbenzene; aliphatic alcohols such as methanol and isopropanol; compounds containing carbonyl groups such as acetic acid, methyl acetate, acetone, dimethyl carbonate, dimethylacetamide, N-methylsuccinimide, and tetramethylurea; nitrile compounds such as acetonitrile, etc. Among these, ketones are preferred from the viewpoint of chain transfer performance and heat resistance of molded products.
[0087] A pH buffer may be added to the reaction system. Examples of the pH buffer include disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium hydrogen carbonate, sodium carbonate, and hydrates thereof.
[0088] As the emulsifier used in the emulsion polymerization, there can be mentioned, for example, hydrocarbon emulsifiers such as sodium lauryl sulfate and sodium dodecylbenzene sulfonate; ammonium perfluorooctanoate, sodium perfluorooctanoate, ammonium perfluorohexanoate, CF3(CF2)2O(CF(CF3)CF2O)2CF(CF3)COONH4, CF3(CF2)2OCF(CF3)CF2OCF(CF3)COONH4, CF3(CF2)2OCF2CF2OCF2COONH4, CF3(CF2)2O(CF2CF2 O)2CF2COONH4, CF3(CF2)3OCF2CF2OCF2COONH4, CF3(CF2)3O(CF2CF2O)2CF2COONH4, CF3(CF2)2OCF2CF2OCF 2COONa, CF3(CF2)2O(CF2CF2O)2CF2COONa, CF3(CF2)3OCF2CF2OCF2COONa, CF3(CF2)3O(CF2CF2O)2CF2COON a. CF3CF2OCF2CF2OCF2COONH4, CF3CF2O(CF2CF2O)2CF2COONH4, CF3CF2OCF2CF2OCF2COONa, CF3CF2O(CF2CF 2O)2CF2COONa, CF3OCF2CF2CF2OCF2COONH4, CF3OCF2CF2CF2OCF(CF3)COONH4, CF3OCF2CF2CF2OCF2COONa, C Fluorine-containing emulsifiers such as F3OCF2CF2CF2OCF(CF3)COONa, CF3O(CF2O)3CF2COONH4, CF3O(CF2O)3CF2COONa, CF3OCF(CF3)CF2OCF(CF3)COONH4, CF3OCF(CF3)CF2OCF(CF3)COONa, CF3O(CF2CF2O)2CF2COONH4, CF3O(CF2CF2O)2CF2COONa, etc. Emulsifiers can be a single species or two or more species can be used in combination. Among these, ammonium perfluorooctanoate, CF3(CF2)3OCF2CF2OCF2COONH4, CF3(CF2)2OCF2CF2OCF2COONH4, CF3CF2OCF2CF2OCF2COONH4, CF3OCF2CF2CF2OCF2COONH4 are preferred.
[0089] The emulsifier may be added all at once or sequentially. The amount of the emulsifier used is preferably 0.01 to 20 parts by mass, more preferably 0.05 to 15 parts by mass, and even more preferably 0.1 to 10 parts by mass, based on 100 parts by mass of the aqueous medium.
[0090] The conditions such as pressure and temperature of the polymerization reaction are appropriately set according to the monomer composition, the decomposition temperature of the radical polymerization initiator, etc. Usually, the pressure is preferably 0.1 to 20 MPaG, more preferably 0.3 to 10 MPaG, and further preferably 0.3 to 5 MPaG. The temperature is preferably 0 to 100° C., more preferably 10 to 90° C., and further preferably 20 to 85° C.
[0091] In the emulsion polymerization, the fluorinated copolymer is obtained in the form of latex, and can be purified by appropriately adding a metal salt, an inorganic acid such as hydrochloric acid or sulfuric acid, aggregating the latex by a known method such as mechanical shearing or freeze-thaw.
[0092] In the case of solution polymerization, purification can be performed by washing with an aqueous medium such as methanol.
[0093] [Fluorinated copolymer composition]
[0094] The fluorinated copolymer composition for obtaining the crosslinked product of the present embodiment is not particularly limited as long as it contains a fluorinated copolymer and a crosslinking agent capable of forming a crosslinked structure containing an indole ring. The fluorinated copolymer composition described in the embodiment of the present invention (hereinafter also referred to as "the composition of the present embodiment") preferably contains a fluorinated copolymer and a compound (D) from the viewpoint of crosslinking reactivity and heat resistance of the crosslinked product, wherein the fluorinated copolymer contains a structural unit (A) derived from TFE, a structural unit (B) derived from at least one of PAVE and PBVE, and a structural unit (C) derived from a fluorinated compound having a carbon-carbon double bond and a -C(=O)CH2- group, wherein the compound (D) has two or more structures (d) represented by the following formula (1).
[0095] That is, the fluorinated copolymer constituting the composition of the present embodiment is preferably equivalent to the fluorinated copolymer used to form the crosslinked product of the present embodiment. Compound (D) acts as a crosslinking agent for the fluorinated copolymer, and the fluorinated copolymer composition of the present embodiment reacts to obtain a crosslinked product having a crosslinked structure containing an indole ring.
[0096]
[0097] In formula (1), -a 1 Represents a single bond, which is bonded to a hydrogen atom, a methyl group or an aromatic ring optionally having a substituent. From the viewpoint of heat resistance of the crosslinked product, the aromatic ring is preferably a monocyclic or condensed ring having 6 to 12 carbon atoms, including a benzene ring or a naphthalene ring and optionally containing a heteroatom. The substituent possessed by the aromatic ring preferably has 1 to 6 carbon atoms, more preferably 1 to 5, and further preferably an alkyl group having 1 to 4 carbon atoms. The alkyl group may be linear or branched.
[0098] -b 1 ~-b 5Respectively represent single bonds, in order to form the indole ring in the cross-linking reaction, -b 1 and -b 5 At least one of them is bonded to a hydrogen atom. 1 or -b 5 Bonded to -a 1 The bonded aryl groups may form a condensed ring including a nitrogen atom.
[0099] From the viewpoint of ease of synthesis and heat resistance of the cross-linked product of the present embodiment, compound (D) preferably has one or more structures in which a benzene ring A of one structure (d) is linked to a benzene ring A of another structure (d) by a single bond.
[0100] In addition, from the viewpoint of crosslinking reactivity, it is preferred that the structure (d) has -a bonded to a hydrogen atom. 1 The hydrazinobenzene skeleton, compound (D) is a hydrazinobenzene skeleton having two structures (d) with -b 1 ~-b 5 A substance obtained by bonding any one of the following.
[0101] Furthermore, compound (D) is more preferably a compound in which two benzene rings A of hydrazinobenzene are bonded to each other by a single bond. The bonding position of the single bond connecting the benzene rings A to each other may be -b 1 ~-b 5 If it is such a structure, the heat stability of the formed cross-linked structure is high, and a cross-linked product with better heat resistance can be obtained.
[0102] Among these, from the viewpoint of thermal stability of the formed cross-linked structure and easy availability of raw materials, compounds in which the hydrazino group is in the para (p-) position relative to the single bond connecting the benzene rings A to each other are preferred, and examples thereof include compounds (CLA-1 to CLA-3) represented by the following formulas, with CLA-1 being particularly preferred.
[0103]
[0104] CLA-1 can be obtained as a hydrochloride salt by, for example, using 4,4'-diiodobiphenyl as a raw material and replacing the iodine atom with a hydrazine group by a known method. CLA-1 can also be obtained as a commercially available product. In addition, CLA-2 can be synthesized by, for example, the method described in the examples, and CLA-3 can also be synthesized by the same method.
[0105] As the compound (D), it is also preferred that two structures (d) are bonded via one or more selected from the group consisting of an oxygen atom, a sulfur atom, a sulfonyl group, a perfluoroalkylene group, a perfluoropolyether group, and a divalent aromatic ring optionally having a substituent.
[0106] Other specific examples of compound (D) are shown below.
[0107]
[0108]
[0109] In the composition of the present embodiment, from the viewpoint of sufficient heat resistance and rubber properties of the cross-linked product, the content of the compound (D) is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 8 parts by mass, and further preferably 0.3 to 5 parts by mass relative to 100 parts by mass of the fluorinated copolymer of the present embodiment. The compound (D) may be used alone or in combination of two or more.
[0110] In the composition of the present embodiment, in the range not damaging the effect of the present invention, in addition to comprising the fluorinated copolymer and compound (D), other additives may also be included. As other additives, for example, crosslinking aids, fillers, reinforcing materials, scorch delay agents, mold release agents, acid acceptors, crown ethers, pigments, etc. may be listed. Various additives may be used alone and selected from one of them, or two or more may be used in combination.
[0111] As a cross-linking aid, from the viewpoint of promoting the cross-linking reaction of the fluorinated copolymer based on compound (D), an acid catalyst is preferably used. It can be considered that if the composition of the present embodiment includes an acid catalyst, the mutual isomerization of the arylhydrazone generated in the system to the isomerization of enehydrazine (Enehydrazine) is promoted, and in addition, the formation of the indole ring is also accelerated. As an acid catalyst, protonic acid and Lewis acid can be listed, specifically, aliphatic carboxylic acids (also including fluorinated fatty acids) such as acetic acid, trifluoroacetic acid, lauric acid, stearic acid, and aromatic carboxylic acids such as benzoic acid can be listed; sulfuric acid, zinc chloride, boron trifluoride diethyl ether complex, polyphosphoric acid, p-toluenesulfonic acid, trifluoromethanesulfonic acid, etc. Among these, from the viewpoint of cross-linking reactivity, aliphatic carboxylic acids, aromatic carboxylic acids, polyphosphoric acid, and p-toluenesulfonic acid are preferably used.
[0112] The crosslinking aid can be added as an additive to the composition, or it can be pre-quaternized with the compound (D) by a known method. As counter anions of the quaternary ammonium cation, carboxylate anions, sulfonate anions, etc. can be listed. From the viewpoint of crosslinking reactivity, it is preferably a conjugated anion of an acid having an acid dissociation constant of 4 or less in water.
[0113] Examples of fillers and reinforcing materials include carbon materials such as carbon black, fullerenes, carbon nanotubes, fluorinated graphite, and fluorinated carbon; fluoropolymers such as polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymers, and ethylene-tetrafluoroethylene copolymers; barium sulfate; calcium metasilicate; metal oxides such as silicon dioxide, titanium oxide, yttrium oxide, and aluminum oxide; metal carbides such as silicon carbide and aluminum carbide; metal nitrides such as silicon nitride and aluminum nitride; imide fillers such as polyimide, polyamide-imide, and polyetherimide; polyaryletherketones such as polyetheretherketone (PEEK), polyetherketone (PEK), and polyetherketoneketone (PEKK); polyesters; polyethersulfone; polyphenylene sulfide; clay; talc, and the like.
[0114] Examples of the scorch retardant include compounds containing a phenolic hydroxyl group such as bisphenol A; quinones such as hydroquinone; and α-methylstyrene dimers such as 2,4-diphenyl-4-methyl-1-pentene.
[0115] Examples of release agents include sodium stearate, examples of acid acceptors include aliphatic polyesters, aliphatic metal salts, and divalent metal oxides such as calcium oxide, zinc oxide, and lead oxide, and examples of crown ethers include 18-crown-6.
[0116] Examples of pigments include inorganic pigments such as zinc flower, titanium dioxide, and carbon black; organic pigments having a diketopyrrolopyrrole skeleton, an isoindolinone skeleton, a quinacridone skeleton, an anthraquinone skeleton, a polyarylene skeleton, and an imide skeleton, etc. Among these, organic pigments are preferred from the viewpoint of improving heat resistance and plasma resistance by quenching ability for free radicals or redox active substances.
[0117] When the composition of the present embodiment contains other additives, the total content of other additives is preferably more than 0 part by mass and 30 parts by mass or less, more preferably 25 parts by mass or less, further preferably 20 parts by mass or less, based on 100 parts by mass of the fluorinated copolymer of the present embodiment.
[0118] As another embodiment of the composition for obtaining the cross-linked product of the present embodiment, there may be mentioned, for example, a composition comprising a fluorinated copolymer comprising a structural unit derived from a fluorinated compound such as CSM-7 to CSM-9, and a compound having an indole ring.
[0119] When such a composition is reacted, a cross-linked product having an indole ring can be obtained, and the cross-linked product has excellent heat resistance.
[0120] Examples of methods for producing a cross-linked product from the composition of the present embodiment include a method in which the components of the fluorinated copolymer composition are mixed using a roll, a kneader, a Banbury mixer, a single-screw or twin-screw kneading extruder, etc., and the resulting mixture is heated, irradiated with radiation, etc., thereby cross-linking the fluorinated copolymer. Preferably, cross-linking is carried out by heating.
[0121] In crosslinking by heating, the fluorinated copolymer can be crosslinked by, for example, heating at 80 to 300° C. for 0.1 to 24 hours. The temperature may be changed to further heat the fluorinated copolymer that has been heated once. That is, after the primary crosslinking, a secondary crosslinking may be performed. From the viewpoint of appropriately performing the crosslinking reaction, for example, a primary crosslinking is preferably performed at 80 to 200° C. for 0.1 to 6 hours, followed by a secondary crosslinking at 200 to 300° C. for 1 to 24 hours. During the primary crosslinking, the mixture may be appropriately molded.
[0122] Examples of the molding method include compression molding, injection molding, extrusion molding, calendar molding, and a method of dissolving in a solvent and then impregnating or applying to a substrate and then molding.
[0123] The crosslinked product of the present embodiment is suitable as a sealing material and buffer material such as an O-ring, a V-ring, a gasket, an oil seal, a gasket, a diaphragm film, and a sheet. In addition, it can be suitably used in various applications such as a heat-resistant chemical-resistant sealing material, a heat-resistant oil-resistant sealing material, a wire covering material, a sealing material for a semiconductor device, a corrosion-resistant rubber coating, a sealing material for a urea-resistant grease, a rubber coating, an adhesive rubber, a hose, a tube, a calendered sheet (roller), a sponge, a rubber roller, a member for oil excavation, a heat sink, a solution crosslinked body, a rubber sponge, a bearing seal, a lining material, an insulating sheet for automobiles, an insulating sheet for electronic equipment, a rubber belt for clocks, a gasket for an endoscope, a bellows hose, a gasket / valve for a water heater, a fender, a fiber / nonwoven fabric (protective clothing, etc.), a base sealing material, a rubber glove, a stator of a uniaxial eccentric screw pump, a component for a urea SCR system, an anti-vibration agent, a shock absorber, a sealant, an additive added to other materials, and a toy.
[0124] Example
[0125] Hereinafter, the present invention will be specifically described based on examples, but the present invention is not limited to the following examples, and various modifications can be made within the scope not departing from the gist of the present invention.
[0126] [Used compounds]
[0127] The following is an explanation of the abbreviations of various compounds used.
[0128] PX1: TFE / PMVE copolymer having iodine atoms at the ends; the molar ratio of structural units derived from TFE and PMVE is 66 / 34, and the iodine atom content is 0.15 mass % (the production method refers to Example 1 of the embodiment of International Publication No. 2018 / 225586)
[0129] ·PX2: TFE / PMVE / CF2=CFO(CF2)3OCF=CF2 copolymer having iodine atoms at the ends; the molar ratio of structural units derived from TFE, PMVE and CF2=CFO(CF2)3OCF=CF2 is 65.9 / 34.0 / 0.1, and the iodine atom content is 0.20% by mass (the production method refers to copolymer 4 of Example 2 of International Publication No. 2020 / 184427 (wherein aggregation with potassium aluminum sulfate is changed to aggregation with nitric acid))
[0130] PX3: TFE / PMVE / CF2=CFO(CF2)3OCF=CF2 copolymer having an iodine atom at the end; the molar ratio of the structural units derived from TFE, PMVE and CF2=CFO(CF2)3OCF=CF2 is 71.40 / 28.43 / 0.17, and the iodine atom content is 0.10 mass% (the production method refers to copolymer 1 of Example 2 of International Publication No. 2020 / 184427)
[0131] · P25B: 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane; "PERHEXA (registered trademark) 25B", manufactured by NOF Corporation
[0132] BOAP: 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, manufactured by Tokyo Chemical Industry Co., Ltd.
[0133] TAIC (registered trademark): Triallyl isocyanurate, manufactured by Tokyo Chemical Industry Co., Ltd.
[0134] ·C6-DV: 1,6-divinylperfluorohexane, manufactured by Tosoh Finechem Corporation.
[0135] FB-BMI: a bismaleimide compound represented by the following formula (see Patent Document 1)
[0136]
[0137] ·2E4MZ: 2-ethyl-4-methylimidazole, manufactured by Tokyo Chemical Industry Co., Ltd.
[0138] CSM-2 to CSM-6: compounds represented by the following formulae; obtained by the same operation as in Synthesis Example 1 below, except that the acetoxy group of the raw material compound was replaced with an acetyl group.
[0139]
[0140] ·CSM-7 to CSM-9: compounds represented by the following formulas; commercially available products
[0141]
[0142] CLA-4 to CLA-6: compounds represented by the following formulas; commercially available products
[0143]
[0144] CLA-8 and CLA-9: compounds represented by the following formulae; obtained by using CLA-5 and CLA-6 as starting compounds and conducting iodination reactions in the same manner as in Synthesis Example 2-4.
[0145]
[0146] ·NaH: Sodium hydride; 60% by mass dispersion in liquid paraffin
[0147] CsF: Cesium fluoride
[0148] [Analysis and measurement methods]
[0149] <Nuclear Magnetic Resonance (NMR) Measurement>
[0150] The synthesized compound was measured using a nuclear magnetic resonance apparatus ("JNM-AL300", manufactured by JEOL Ltd.; the same applies hereinafter). 1 H-NMR and 19 F-NMR and structural analysis.
[0151] <Mass spectrometry (MS)>
[0152] The molecular weight was determined using a gas chromatograph-mass spectrometer ("GCMS-QP2010 Ultra", manufactured by Shimadzu Corporation; chemical ionization method (CI)).
[0153] <Content of Monomer Structural Units in Fluorinated Copolymer>
[0154] According to the NMR measurement device 1 H-NMR and 19 From the results of F-NMR measurement, the content (mass ratio and molar ratio) of the monomer structural unit in the fluorinated copolymer was calculated.
[0155] A 1H-perfluorohexane solution of a fluorinated copolymer and 1,4-bis(trifluoromethyl)benzene (standard substance) was used as a measurement sample.
[0156] The content of the PAVE structural units (PMVE and PPVE) in the fluorinated copolymer was calculated from the integrated ratio of the peak of fluorine atoms attributable to the trifluoroalkyl group of PAVE to the peak of fluorine atoms attributable to the trifluoromethyl group of 1,4-bis(trifluoromethyl)benzene.
[0157] The content of the PBVE structural unit in the fluorinated copolymer was calculated as the integrated ratio of the peak of fluorine atoms attributable to fluoromethine groups and the peak of fluorine atoms attributable to trifluoromethyl groups of 1,4-bis(trifluoromethyl)benzene, and converted into the content.
[0158] The content of each structural unit of CSM-1 to CSM-6 in the fluorinated copolymer was converted from the integrated ratio of the peak of hydrogen atoms attributed to the methyl groups of CSM-1 to CSM-6 to the peak of hydrogen atoms attributed to the aromatic ring of 1,4-bis(trifluoromethyl)benzene.
[0159] The content of each structural unit of CSM-7 and CSM-8 in the fluorinated copolymer was calculated by calculating the integrated ratio of the peaks attributable to the fluorine atoms of the difluoroiodomethyl groups of CSM-7 and CSM-8 and the peaks attributable to the fluorine atoms of the trifluoromethyl groups of 1,4-bis(trifluoromethyl)benzene, and converting the ratio into the content.
[0160] The content of the CSM-9 structural unit in the fluorinated copolymer was calculated by calculating the integrated ratio of the peak of fluorine atoms attributable to fluorocarbonyl groups of CSM-9 to the peak of fluorine atoms attributable to trifluoromethyl groups of 1,4-bis(trifluoromethyl)benzene.
[0161] The content of 8CNVE structural units in the fluorinated copolymer was calculated from the integrated ratio of the peak attributed to the fluorine atoms of the difluoromethylene groups adjacent to the nitrile groups of 8CNVE to the peak attributed to the fluorine atoms of the trifluoromethyl groups of 1,4-bis(trifluoromethyl)benzene.
[0162] The content of TFE in the fluorinated copolymer is determined as the remainder of the contents of the above-mentioned respective structural units in the fluorinated copolymer.
[0163] [Synthesis of Monomer]
[0164] (Synthesis Example 1) Synthesis of CSM-1
[0165]
[0166] 107 g (350 mmol) of the raw material compound (1) and 750 mL of diethyl ether were added to a 2 L four-necked flask, and the reaction solution was cooled to below -65°C using a dry ice / acetone bath. The reaction solution was kept below -60°C, and 436 mL (about 3 mol / L) of a 35% by mass methylmagnesium bromide diethyl ether solution was added dropwise over 2 hours, and the mixture was allowed to react for 4 hours. The reaction solution was kept below -38°C, and a mixture of 150 mL of hydrochloric acid and 150 mL of tetrahydrofuran, which were cooled to 5°C and had a concentration of 36% by mass, was added dropwise over 2.5 hours.
[0167] The product was returned to room temperature, 170 mL of ion exchange water was added and the liquid was separated to recover the organic phase. 170 mL of diethyl ether was added to the aqueous phase and extracted, and the organic phase was merged with the previous organic phase. The obtained organic phase was washed with 170 mL of 5 mass % sodium bicarbonate aqueous solution, then, after washing with 170 mL of saturated brine, anhydrous sodium sulfate was added to dry. After removing the residue by vacuum filtration, the evaporator was concentrated under reduced pressure (27 kPa) at 35 ° C. The concentrate was transferred to a 200 mL eggplant flask, a Wei's fractionation column was installed, and purified by vacuum distillation to obtain CSM-1 68 g (yield was 68%).
[0168] The data for identification of CSM-1 are shown below. It should be noted that the symbols denoted for fluorine atoms (F) correspond to the symbols in the above formula (I).
[0169] 1 H-NMR(CDCl3): δ[ppm]2.46(s,3H)
[0170] 19 F-NMR (CDCl3): δ[ppm]-85.3(m,2F,F-3),-113.6(dd,1F,J=65.6,82.4Hz,F-1b),-121.4(t,2F,J=9.16Hz,F-5 ),-121.8(ddt,1F,J=6.10,83.9,112.9,F-1a),-126.5(s,2F,F-4),-135.4(ddt,1F,J=6.10,65.6,112.9,F-2)
[0171] MS (CI) m / z: 291 (M+H + )
[0172] [Synthesis of cross-linking agent]
[0173] (Synthesis Example 2-1) Synthesis of CLA-1
[0174]
[0175] Under a nitrogen atmosphere, 25.0 g (1.6 mmol) of 4,4'-diiodobiphenyl, 170 mL of dimethyl sulfoxide (DMSO), 19.5 g (148 mmol) of tert-butyl carbazate (BocNHNH2), 1.17 g (6.14 mmol) of copper (I) iodide and 60.2 g (185 mmol) of cesium carbonate were added to a 1 L four-necked flask, and the reaction was carried out in an oil bath at a liquid temperature of 54°C for 21 hours.
[0176] The reaction solution was returned to room temperature, 600 mL of ion exchange water was added, and the mixture was stirred for 30 minutes. The precipitated solid was recovered by vacuum filtration and dried under reduced pressure to obtain a crude solid.
[0177] The crude solid and the filtrate were purified by heating under reflux and drying under reduced pressure, respectively, to obtain 12.4 g (yield 49%) of compound (2) as a light yellow solid.
[0178] The data for identification of compound (2) are shown below.
[0179] 1 H-NMR (DMSO-d6): δ [ppm] 7.58 (d, 4H, J = 8.54Hz, Ar-H), 7.54 (d, 4H, J = 8.54Hz, Ar-H), 5.09 (s, 4H, NH2), 1.47 (s, 18H, N-Boc)
[0180]
[0181] Next, in a nitrogen atmosphere, 8.87 g (21.4 mmol) of compound (11) and 107 mL of dichloromethane were added to a 500 mL four-necked flask, and 93 mL (about 4 mol / L) of a hydrogen chloride 1,4-dioxane solution was added dropwise while cooling in an ice bath, and the mixture was returned to room temperature and allowed to react for 14 hours. The precipitated solid was recovered by vacuum filtration, washed with diethyl ether, and dried under reduced pressure to obtain 5.76 g (yield: 94%) of CLA-1 hydrochloride.
[0182] Under nitrogen atmosphere, CLA-1 hydrochloride 5.00 g (17.35 mmol), dichloromethane 30 mL and 10 mass % sodium hydroxide aqueous solution 20 mL were added to a 100 mL four-necked flask and stirred at room temperature for 1 hour. The precipitated solid was recovered by vacuum filtration, washed with ion exchange water and dried under reduced pressure to obtain CLA-1 3.36 g (yield 90%).
[0183] The data in the identification of CLA-1 hydrochloride and CLA-1 are shown below. It should be noted that the symbols marked for hydrogen atoms (H) correspond to those in the above formula (II-1).
[0184] <CLA-1 hydrochloride>
[0185] 1 H-NMR (DMSO-d6): δ [ppm] 10.3 (s, 6H, -NH3Cl), 8.35 (s, 2H, -NH-), 7.57 (d, 4H, J = 8.54 Hz, H-1), 7.05 (d, 4H, J = 8.54 Hz, H-2)
[0186] <cla-1>
[0187] 1 H-NMR (DMSO-d6): δ [ppm] 7.31 (d, 4H, J = 8.54Hz, Ar-H), 6.79 (d, 4H, J = 8.54Hz, Ar-H), 6.64 (s, 2H), 3.93 (s, 4H)
[0188] (Synthesis Example 2-2) Synthesis of CLA-2 (hydrochloride)
[0189]
[0190] Into a 100 mL four-necked flask, 14.1 mL of hydrochloric acid at a concentration of 20% by mass was added, cooled in an ice bath, and 2.00 g (6.25 mmol) of compound (12) (manufactured by Tokyo Chemical Industry Co., Ltd.) was added while stirring. While the reaction solution was kept below 2.5°C, an aqueous solution obtained by dissolving 0.89 g (12.9 mmol) of sodium nitrite in 20 mL of ion exchange water was added dropwise over 2 hours, and then stirred for 30 minutes. Next, a mixed solution of 6.85 g (30.4 mmol) of tin (II) chloride dihydrate and 8.7 mL of hydrochloric acid at a concentration of 36% by mass was added dropwise over 2 hours, and then stirred for 45 minutes.
[0191] The precipitated solid was recovered by vacuum filtration and dried under reduced pressure at 35°C to obtain 0.485g of a crude product. 20mL of chloroform and 11mL of 0.5mol / L sodium hydroxide aqueous solution were added to the crude product, and the organic phase was separated. 20mL of chloroform was added to the aqueous phase and extracted again, and combined with the previous organic phase. Anhydrous sodium sulfate was added to the obtained organic phase for drying. After removing the residue by vacuum filtration, the evaporator was used to concentrate under reduced pressure at 30°C. The concentrate was separated and purified by silica gel column chromatography ("Silica Gel 60 (spherical) NH2", manufactured by Kanto Chemical Co., Ltd., 16g; mobile phase: chloroform; the same below.) to obtain CLA-2 97.6mg.
[0192] CLA-2 (97.6 mg), diethyl ether (4 mL), and about 1 mol / L hydrogen chloride diethyl ether solution (1 mL) were placed in a 50 mL eggplant-shaped flask and stirred.
[0193] The precipitated solid was recovered by filtration under reduced pressure and dried under reduced pressure to obtain 74.7 mg of CLA-2 hydrochloride (yield: 3%).
[0194] The data for identification of CLA-2 and CLA-2 hydrochloride are shown below: It should be noted that the symbols denoted for hydrogen atoms (H) correspond to the symbols in the above formula (II-2).
[0195] <cla-2>
[0196] 1 H-NMR(CDCl3): δ [ppm] 7.18 (d, 2H, J = 2.56 Hz, H-3), 7.12 (d, 2H, J = 7.68 Hz, H-1), 6.94 (dd, 2H, J = 2.56, 8.54 Hz, H-2), 5.40 (brs, 2H, -NHNH2), 3.66 (brs, 4H, -NHNH2)
[0197] 19 F-NMR(CDCl3): δ [ppm] -59.0 (s, 6F, -CF3)
[0198] <CLA-2 Hydrochloride>
[0199] 1 H-NMR(DMSO-d6): δ [ppm] 10.39 (brs, 6H, -NHNH3Cl), 8.81 (brs, 2H, -NHNH3Cl), 7.39 (d, 2H, J = 2.56 Hz, H-3), 7.3 - 7.2 (m, 4H, H-1 and H-2)
[0200] 19 F-NMR(DMSO-d6): δ [ppm] -56.7 (s, 6F, -CF3)
[0201] (Synthesis Example 2-3) Synthesis of CLA-3 (Hydrochloride)
[0202]
[0203] Charge 6.8 mL of 20 mass% hydrochloric acid into a 100 mL four-necked flask, cool it using an ice bath, and add 1.00 g (2.99 mmol) of Compound (13) (manufactured by Tokyo Chemical Industry Co., Ltd.) while stirring. While maintaining the reaction solution at 2.0 °C or lower, add dropwise over 2 hours an aqueous solution obtained by dissolving 0.43 g (6.16 mmol) of sodium nitrite in 9.5 mL of ion-exchanged water, and then stir for 1 hour. Next, add dropwise over 2 hours a mixed solution of 3.28 g (14.5 mmol) of tin(II) chloride dihydrate and 4.2 mL of 36 mass% hydrochloric acid, and then stir for 30 minutes.
[0204] The precipitated solid was recovered by vacuum filtration and dried under reduced pressure at 35°C to obtain 0.269g of a crude product. 10mL of chloroform and 6mL of 0.5mol / L sodium hydroxide aqueous solution were added to the crude product, and the organic phase was separated. 15mL of chloroform was added to the water layer and extracted again, and combined with the previous organic phase. Anhydrous sodium sulfate was added to the obtained organic phase for drying. After removing the residue by vacuum filtration, the evaporator was concentrated under reduced pressure at 30°C. The concentrate was separated and purified by silica gel column chromatography to obtain 22.8mg of CLA-3.
[0205] 22.8 mg of CLA-3, 1 mL of diethyl ether, and 0.25 mL of an approximately 1 mol / L hydrogen chloride diethyl ether solution were placed in a 10 mL eggplant-shaped flask and stirred.
[0206] The precipitated solid was recovered by filtration under reduced pressure and dried under reduced pressure to obtain 14.9 mg (yield: 1%) of CLA-3 hydrochloride as a light yellow solid.
[0207] <cla-3>
[0208] 1 H-NMR (CDCl3): δ [ppm] 7.2 - 7.3 (m, 4H, H-1), 6.78 (d, 4H, J = 9.39 Hz, H-2), 5.31 (brs, 2H, -NHNH2), 3.60 (brs, 4H, -NHNH2)
[0209] 19 F-NMR (CDCl3): δ [ppm] -64.8 (s, 6F, -CF3)
[0210] <CLA-3 Hydrochloride>
[0211] 1 H-NMR (DMSO-d6): δ [ppm] 10.34 (brs, 6H, -NHNH3Cl), 8.65 (brs, 2H, -NHNH3Cl), 7.23 (d, 4H, J = 8.54 Hz, H-1), 7.03 (d, 4H, J = 8.54 Hz, H-2)
[0212] 19 F-NMR (DMSO-d6): δ [ppm] -62.9 (s, 6F, -CF3)
[0213] (Synthesis Example 2-4) Synthesis of CLA-7
[0214]
[0215] In a 5 mL round-bottom flask, 100 mg (0.64 mmol) of CLA-4 was dissolved in 2 mL of dimethyl sulfoxide, 303 mg (1.34 mmol) of N-iodosuccinimide (NIS) was added, and the mixture was stirred at room temperature for 24 hours. 20 mL of ethyl acetate was added to the reaction solution, and it was washed with a saturated aqueous solution of sodium thiosulfate. The organic phase was separated, dried over anhydrous sodium sulfate, and the solvent was removed by distillation under reduced pressure. Purification was carried out by silica gel column chromatography to obtain CLA-7.
[0216] [Manufacture of Fluorine-containing Copolymer]
[0217] (Synthesis Example 3-1) Emulsion Polymerization (1)
[0218] After degassing a stainless steel autoclave with a volume of 200 mL and a stirrer, 82 g of ion exchange water, 0.023 g (0.065 mmol) of disodium hydrogen phosphate dodecahydrate, 10.2 g (8.3 mmol) of 30% by mass CF3CF2OCF2CF2OCF2COONH4 aqueous solution, 0.062 g (0.27 mmol) of ammonium persulfate and 0.082 g (0.27 mmol) of CSM-1 were added to replace the gas phase with nitrogen. While stirring the reaction solution at 300 rpm, 1.4 g (14 mmol) of TFE and 6.5 g (39 mmol) of PMVE were pressed into the autoclave, and the liquid temperature was raised to 80°C. The internal pressure of the autoclave was 0.8 MPaG. As a result of stirring at 300 rpm for 4 hours while maintaining the liquid temperature, the internal pressure dropped to 0.6 MPaG. After the residual gas in the gas phase was released, the autoclave was opened to obtain a latex containing a fluorinated copolymer.
[0219] After freezing the latex, it was thawed to aggregate the fluorinated copolymer. The fluorinated copolymer was filtered, washed with ion-exchanged water and then with methanol, and vacuum-dried at 50°C to obtain 1.9 g of a white fluorinated copolymer (P1).
[0220] The contents (mass ratio) of the structural units derived from TFE, PMVE and CSM-1 in the obtained fluorinated copolymer (P1) were 56.7 / 42.3 / 1.0 (molar ratio: 69.0 / 30.6 / 0.4).
[0221] (Synthesis Example 3-2) Emulsion Polymerization (2)
[0222] In Synthesis Example 3-1, the amount of ammonium persulfate was set to 0.030 g (0.13 mmol), and the temperature of the liquid after TFE and PMVE were pressed into the autoclave was maintained at 65° C., and polymerization was carried out in the same manner as in Synthesis Example 3-1 to obtain a latex containing a fluorinated copolymer, thereby obtaining 0.68 g of a white fluorinated copolymer (P2). It should be noted that during the polymerization reaction, the internal pressure of the autoclave was reduced from 0.7 MPaG to 0.6 MPaG.
[0223] The contents (mass ratio) of the structural units derived from TFE, PMVE and CSM-1 in the obtained fluorinated copolymer (P2) were 52.8 / 40.8 / 6.4 (molar ratio: 68.2 / 29.1 / 2.7).
[0224] (Synthesis Example 3-3) Solution Polymerization (1)
[0225] Into a stainless steel autoclave with an internal volume of 200 mL and a stirrer, 1.2 g (3.8 mmol) of CSM-1, 0.5 g (1.5 mmol) of bis (pentafluoropropionyl) peroxide, a 1H-perfluorohexane solution with a concentration of 2.8% by mass, and 57 g of 1H-perfluorohexane were added, and freeze degassing was performed twice. While stirring the reaction solution at 300 rpm, 15 g (0.15 mol) of TFE and 103 g (0.62 mol) of PMVE were pressed into the autoclave, and the liquid temperature was maintained at 28 ° C. The internal pressure of the autoclave was 0.7 MPaG. While maintaining the liquid temperature, the internal pressure was reduced to 0.5 MPaG as a result of stirring at 300 rpm for 24 hours. After releasing the residual gas in the gas phase, the autoclave was opened to obtain a solution containing a fluorinated copolymer.
[0226] The obtained solution containing the fluorinated copolymer was vacuum dried to obtain a viscous liquid. The liquid was dissolved in 200 mL of 1H-perfluorohexane, and the solution was added to 1 L of methanol and stirred for 30 minutes to generate a white solid. A centrifuge was used to separate the solid and the supernatant. The obtained solid was vacuum dried at 50°C to obtain 37.1 g of a white fluorinated copolymer (P3).
[0227] The contents (mass ratio) of the structural units derived from TFE, PMVE and CSM-1 in the obtained fluorinated copolymer (P3) were 56.1 / 42.8 / 1.1 (molar ratio: 68.5 / 30.5 / 1.0).
[0228] (Synthesis Example 3-4) Solution Polymerization (2)
[0229] In Synthesis Example 3-3, except that the amount of CSM-1 was set to 12 g (38 mmol), polymerization was carried out in the same manner as in Synthesis Example 3-3 to obtain a solution containing a fluorinated copolymer, thereby obtaining 3.2 g of a white fluorinated copolymer (P4). It should be noted that during the polymerization reaction, the internal pressure of the autoclave was reduced from 0.7 MPaG to 0.5 MPaG.
[0230] The contents (mass ratio) of the structural units derived from TFE, PMVE and CSM-1 in the obtained fluorinated copolymer (P4) were 52.3 / 38.5 / 9.2 (molar ratio: 69.3 / 21.7 / 9.0).
[0231] (Synthesis Example 3-5) Modification of FFKM using CSM-1 (1)
[0232] PX1 34g, CSM-1 32g (0.11mol), lauroyl peroxide 0.88g (2.2mmol) and 1H-perfluorohexane 135g were added to a stainless steel autoclave with an internal volume of 200mL and equipped with a stirrer, and freeze-degassing was performed twice. The reaction solution was stirred at 300rpm while the liquid temperature was raised to 90°C, and stirred at 300rpm for 4 hours while maintaining the liquid temperature. The autoclave was cooled to room temperature and opened to obtain a solution containing a fluorinated copolymer.
[0233] The obtained solution containing the fluorinated copolymer was vacuum dried to obtain a white solid. The solid was dissolved in 1 L of 1H-perfluorohexane, and the solution was added to 5 L of methanol and stirred for 5 minutes to generate a white solid. The solid was filtered, washed with methanol, and then vacuum dried at 50°C to obtain 29 g of a white fluorinated copolymer (P5) (CSM-1 content was 0.4% by mass).
[0234] (Synthesis Example 3-6) Modification of FFKM using CSM-1 (2)
[0235] A solution containing a fluorinated copolymer was obtained in the same manner as in Synthesis Example 3-5 except that PX2 was used instead of PX1, to thereby obtain 24 g of a white fluorinated copolymer (P6) (CSM-1 content: 0.4 mass %).
[0236] (Synthesis Example 3-7) Fluorinated copolymer having nitrile group
[0237] After degassing a stainless steel autoclave with a volume of 2 L and equipped with a stirrer, 880 g of a 30% by mass aqueous solution of C2F5O(CF2)2OCF2COONH4, 7.3 g (18.8 mmol) of CF2=CFOCF2CF(CF3)OCF2CF2CN (hereinafter referred to as 8CNVE) and 15.9 g of a 5% by mass aqueous solution of disodium hydrogen phosphate·12-hydrate were added, and the gas phase was replaced with nitrogen. While stirring the reaction solution at 375 rpm, 137 g (1.37 mol) of TFE and 635 g (3.82 mol) of PMVE were pressed into the autoclave, and the liquid temperature was raised to 80°C. The internal pressure of the autoclave was 0.90 MPaG. While maintaining the liquid temperature, 28 mL of a 3% by mass aqueous solution of ammonium persulfate was added to start polymerization.
[0238] When the internal pressure dropped to 0.89 MPaG, 119.3 g of TFE, 3.7 g of 8CNVE, 74 g of PMVE, and 3.7 g of 8CNVE were sequentially pressed in. This operation was repeated for 9 cycles, and then 119.3 g of TFE was pressed in, and the reaction was allowed to proceed for 375 minutes. When the polymerization rate dropped, a 3% by mass aqueous solution of ammonium persulfate was appropriately added. The total amount of the 3% by mass aqueous solution of ammonium persulfate added after the start of the polymerization was 35 mL.
[0239] The autoclave was cooled to lower the liquid temperature to 10°C, thereby obtaining a latex containing a fluorinated copolymer.
[0240] The latex was added to a 5 mass % aqueous solution of potassium aluminum sulfate to aggregate the fluorinated copolymer. The fluorinated copolymer was filtered, washed with ion-exchanged water, and vacuum-dried at 50°C to obtain a white fluorinated copolymer (P7).
[0241] The contents (mass ratio) of the structural units derived from TFE, PMVE and 8CNVE in the obtained fluorinated copolymer (P7) were 56.8 / 41.3 / 1.9 (molar ratio: 69.1 / 30.3 / 0.6).
[0242] (Synthesis Example 3-8) Solution Polymerization (3)
[0243] After degassing a stainless steel autoclave with a volume of 200 mL and a stirrer, PPVE, CSM-1, peroxydicarbonate, methanol, and pre-freeze-degassed 1H-perfluorohexane were added and freeze-degassed twice. While stirring the reaction solution at 300 rpm, TFE was pressed into the autoclave and the liquid temperature was raised to 45° C. While maintaining the liquid temperature, the reaction was stirred at 300 rpm for 6 hours.
[0244] Methanol was added to the product to aggregate the fluorinated copolymer, which was collected by filtration, washed with methanol and dried to obtain a fluorinated copolymer (P8).
[0245] (Synthesis Example 3-9) Solution Polymerization (4)
[0246] A fluorinated copolymer (P9) was obtained in the same manner as in Synthesis Example 3-8, except that PBVE was used instead of PPVE.
[0247] (Synthesis Examples 3-10 to 3-17) Emulsion Polymerization
[0248] Fluorinated copolymers (P10) to (P17) were obtained in the same manner as in Synthesis Example 3-1, except that CSM-2 to CSM-9 were used instead of CSM-1, respectively.
[0249] [Manufacture of cross-linked products]
[0250] (Example 1)
[0251] 100 parts by mass of the fluorinated copolymer (P1), 2.5 parts by mass of CLA-1 and 2.5 parts by mass of acetic acid were kneaded using a twin-screw kneader ("HAAKE (registered trademark) MiniLab3", manufactured by Thermo Fisher Scientific). Using a mold having a length of 100 mm, a width of 60 mm and a thickness of 1 mm, a heat compression press ("SA-401", manufactured by Tester Sangyo Co., Ltd.; the same below) was used to heat-press the kneaded composition for 3 hours under the conditions of 1 MPa and 90° C. in an atmospheric atmosphere to perform primary crosslinking. Furthermore, the composition was heated at 240° C. for 3 hours in an oven ("KDF-75", manufactured by Yamato Scientific Co., Ltd.; the same below) to perform secondary crosslinking to obtain a crosslinked product containing an indole ring structure.
[0252] (Examples 2~6)
[0253] A cross-linked product was produced in the same manner as in Example 1 according to the compounding composition and the conditions of the primary cross-linking and the secondary cross-linking shown in Table 1 below.
[0254] It should be noted that in Example 6, the secondary crosslinking was carried out as follows: after heating at 90°C for 2 hours, the temperature was raised to 200°C over 2 hours, and heated at 200°C for 4 hours. Furthermore, the temperature was raised to 305°C over 2 hours, and heated at 305°C for 12 hours.
[0255] (Example 7)
[0256] The fluorinated copolymer (P8) and CLA-1 were ground in an agate mortar and placed in a glass flask equipped with a magnetic rotor. Lauric acid and methanol were added and stirred for 3 minutes. The mixed solution was decompressed at 25°C.
[0257] The liquid was distilled off to obtain a powder composition.
[0258] The obtained powder composition was put into a mold and heat-pressed for 1 hour in an atmospheric atmosphere at a pressure of 1 MPa and 120° C. using a heat compression press to perform primary crosslinking. Furthermore, it was heated in an oven at 240° C. for 3 hours to perform secondary crosslinking to obtain a crosslinked product.
[0259] (Examples 8~13)
[0260] A cross-linked product was produced in the same manner as in Example 7 except that the fluorinated copolymers (P9) to (P14) were used instead of the fluorinated copolymer (P8).
[0261] (Examples 14~22)
[0262] According to the compounding composition shown in the following Table 3, a cross-linked product was produced in the same manner as in Example 1.
[0263] [Evaluation of heat resistance of cross-linked products]
[0264] Heat resistance of test pieces (20 mm in length, 4 mm in width, 1 mm in thickness) cut out from the crosslinked fluorinated copolymer obtained in each example was evaluated by the following two methods. The evaluation results are shown in Tables 1 to 3. Examples 1, 2, and 7 to 22 are Examples, and Examples 3 to 6 are Comparative Examples.
[0265] <Thermomechanical Analysis (TMA)>
[0266] According to JIS K 7244-4:1999, a thermomechanical analyzer ("TA7000", manufactured by Hitachi High-Tech Science Corporation) was used to raise the temperature of the test piece from the test start temperature of -40°C to 330°C at 5°C / min, and then the temperature was maintained at 330°C for 30 minutes to observe whether the test piece was broken and measure the storage modulus. The test results were evaluated according to the following evaluation criteria.
[0267] (Evaluation Criteria)
[0268] A: The test piece was not broken, and no change in the storage modulus was observed. No decrease.
[0269] B: The test piece was not broken, but the storage modulus decreased.
[0270] C: The test piece is broken.
[0271] The heat resistance evaluation based on TMA can be said to be an index of short-term heat resistance, and the evaluation A was judged as good, the evaluation B was judged as almost good, and the evaluation C was judged as poor.
[0272] <Suspension method>
[0273] A stainless steel wire (1 mm diameter) was passed through the test piece at a portion 3 mm from one end in the longitudinal direction, and the test piece was suspended and placed in an oven ("KDF-75", manufactured by Yamato Scientific Co., Ltd.), and heated under the conditions shown in Table 1 under a nitrogen atmosphere, and then taken out to observe whether the test piece was deformed. The test results were evaluated according to the following evaluation criteria.
[0274] (Evaluation Criteria)
[0275] A: The test piece was not deformed.
[0276] C: The test piece is deformed.
[0277] The heat resistance evaluation by the hanging method can be said to be an index of long-term heat resistance, and the evaluation A was judged as good, and the evaluation C was judged as poor.
[0278] [Table 1]
[0279] Table 1
[0280]
[0281] Note) *90℃ 2h→Heat up 2h→200℃ 4h→Heat up 2h→305℃ 12h
[0282] [Table 2]
[0283] Table 2
[0284]
[0285] [Table 3]
[0286] Table 3
[0287]
[0288] As is apparent from the evaluation results shown in Tables 1 to 3, the cross-linked products of the fluorinated copolymers of the present invention (Examples 1, 2, and 7 to 22) were excellent in both short-term heat resistance and long-term heat resistance.
Claims
1. A cross-linked product of a fluorinated copolymer having an indole ring.
2. The cross-linked product of the fluorinated copolymer according to claim 1, wherein The fluorine-containing copolymer comprises a structural unit (C) derived from a fluorine-containing compound having a carbon-carbon double bond and a -C(=O)CH2- group.
3. The cross-linked product of the fluorinated copolymer according to claim 2, wherein The content of the structural unit (C) is 0.1 to 20 mass % in 100 mass % of the total monomer structural units of the fluorinated copolymer.
4. The cross-linked product of the fluorinated copolymer according to claim 2 or 3, wherein The fluorine-containing copolymer comprises at least one of a structural unit (A) derived from tetrafluoroethylene and a structural unit (B) derived from at least one of a perfluoroalkyl vinyl ether and a perfluorobutenyl vinyl ether.
5. The cross-linked product of the fluorinated copolymer according to claim 4, wherein In the total of 100 mass % of the structural units (A) to (C) of the fluorinated copolymer, the structural unit (A) accounts for 29.9 to 80 mass %, the structural unit (B) accounts for 19.9 to 70 mass %, and the structural unit (C) accounts for 0.1 to 20 mass %.
6. The cross-linked product of the fluorinated copolymer according to claim 4, wherein In the total of 100 mass % of the structural units (A) to (C), the structural unit (A) accounts for 80 to 99.9 mass %, the structural unit (B) accounts for 0 to 19.9 mass %, and the structural unit (C) accounts for 0.1 to 20 mass %.
7. The cross-linked product of the fluorinated copolymer according to claim 4, wherein In 100% by mass of the total of the structural units (A) to (C), the structural unit (A) is 0 to 49.9% by mass, the structural unit (B) is 50 to 99.9% by mass, and the structural unit (C) is 0.1 to 10% by mass.
8. A fluorinated copolymer composition comprising a fluorinated copolymer and a compound (D), wherein the fluorinated copolymer comprises a structural unit (A) derived from tetrafluoroethylene, a structural unit (B) derived from at least any one of a perfluoroalkyl vinyl ether and a perfluorobutenyl vinyl ether, and a structural unit (C) derived from a fluorinated compound having a carbon-carbon double bond and a -C(=O)CH2- group, wherein the compound (D) has two or more structures (d) represented by the following formula (1), In formula (1), -a 1 represents a single bond, which is bonded to a hydrogen atom, a methyl group, or an aromatic ring which may have a substituent; -b 1 ~-b 5 Respectively represent single bonds, -b 1 and -b 5 At least any one of is bonded to a hydrogen atom; In addition, the benzene ring in the formula (1) is referred to as benzene ring A.
9. The fluorinated copolymer composition according to claim 8, wherein The compound (D) has one or more structures in which one benzene ring A of the structure (d) is connected to another benzene ring A of the structure (d) via a single bond.
10. The fluorinated copolymer composition according to claim 8 or 9, wherein The content of the compound (D) is 0.1 to 10 parts by mass based on 100 parts by mass of the fluorinated copolymer.
Citation Information
Patent Citations
Vulcanizable fluorinated copolymer
JP1988005409B2
Vulcanizable perfluoro elastomer
JP1990059177B2
Fluorine-containing elastic copolymer and production method therefor
WO2018225586A1
Fluorine-containing copolymer composition and cross-linked product thereof, and compound
WO2021166664A1
Fluorocopolymer composition and crosslinked rubber article
WO2021210503A1